DiscountCity - über die Geschichte und Zukunft der Stadt des Einzelhandels - Stippich, Matthias (KIT Scientific Publishing, 2014)
Are discount chains responsible for 'sellout' of the classical city? What kind of city do they endorse and what forms of urbanization do they really engender? Can planning practices still intervene to steer the course of urban development? How can concepts of sustainable architecture and urban design be effectively incorporated in the retail sector? This book offers an alternative understanding of the notion of 'DiscountCity' that serves as the basis for future-oriented and collective action.